COVID-19 infection presenting as pancreatitis in a pregnant woman: A case report (2020)
Background: The coronavirus 2019 (COVID-19) pandemic has posed unique challenges in healthcare. In obstetrics, there is little information available to guide practice. As new data emerge, the spectrum of initial presenting symptoms has expanded from fever, cough, and dyspnea to gastrointestinal and other symptoms in both pregnant and non-pregnant patients. Case: A 36-year-old woman, G4P2, at 33 weeks of gestation presented very early in the COVID-19 course with four days of cough and fever, without recent travel or known exposure. She appeared well, with stable vital signs, and was sent home to self-quarantine after a specimen for COVID-19 testing was collected. Two days later, she presented with nausea, vomiting, and abdominal pain, and was diagnosed with acute pancreatitis. Conclusion: To date, no cases of human pancreatitis have been identified as related to a COVID-19 infection, although multiple other gastrointestinal symptoms have been described. Given the lack of other etiology, we consider the possibility that patient's acute pancreatitis could be secondary to COVID-19 infection.